Comparing Direct Numerical Modeling Predictions With Field Evidence for Methane Vertical Microseepage in Two Geological Settings - Costanzo-Álvarez, Vincenzo; Mendoza, Jorge; Aldana, Milagrosa; Jacome, Maria; Díaz, Marisel; Ramirez, Keyla; Amon, Cristina H. (Frontiers in Earth Science, 2022)
The footprints of petroleum microseepage can be associated with chemical and microbial processes in initially homogeneous strata and/or with the fluid transport properties of the rocks through which oil and gas migrate. This work examines the role of such driving factors in two contrasting geological settings by comparing numerical modeling predictions for upward methane microseepage with some field evidence for hydrocarbons transport and accumulation. The two case studies are a monitoring borehole (BH8) from a landfill in southern Ontario, Canada, and an oil well (Saltarin 1A) from the Eastern Llanos Basin in Colombia. Profiles of relative methane concentrations versus depth were generated using a time-dependent, one-dimensional, simulation of the advection-diffusion equation applied to multiple strata of soils and sediments. The model employs the layered sequences of these two geological settings. The results obtained hinge on the standard permeability values for the rock types involved and their corresponding flow velocities and diffusion coefficients. Resistivity logs were utilized as direct proxies of hydrocarbon concentrations. As additional evidence for petroleum microseepage, experiments of electron paramagnetic resonance (EPR) were carried out in drilling cuts of Saltarin 1A to measure traces of organic matter free radicals concentrations (OMFRC). Extractable organic matter (EOM) and magnetic susceptibility data were also considered in interpreting the EPR results. Qualitative comparisons between modeled methane profiles and their corresponding resistivity logs suggest that microseepage and hydrocarbon accumulations are conditioned by the fluid transport properties of the rocks contained by BH8 and Saltarin 1A. Moreover, in most of the Saltarin 1A sequence, the OMFRC profiles follow the trends displayed by the resistivity and modeled methane logs. Thus, the EPR data also indicates that hydrocarbon microseepage and accumulation are largely controlled by lithology. Conversely, EOM and magnetic susceptibility appear to be evidence for hydrocarbon-mediated near-surface chemical processes.